(untitled) (European Journal of Health Research, 2019)
Children´s perceived parental support has been related to frequency and intensity of physical activity in children and adolescents. In recent years, socioecological theories show that family influences could affect, through direct and indirect ways, in this healthy behavior. In this study, 570 students (52.63% girls) of Compulsory Secondary Education reported perceived maternal and paternal instrumental support, modeling and limits to sedentary behavior, self-efficacy, perceived barriers to physical activity and weekly moderate-to-vigorous physical activity. Results showed that different ways of perceived parental support were positively related with physical activity. Moreover, self-efficacy mediated the relationship between perceived parental support and physical activity as perceived barriers to physical activity did not. These finding points to the need to consider different personal mediating variables to know how adolescents ‘perceived parental support is related with physical activity, both inside and outside adolescents´ school context.